Analisis Keterkaitan Budi Daya Petani terhadap Penyakit Tular Tanah Lada di Bangka: Analysis of the Correlation between Farmers' Cultivation and Soil-borne Diseases of Pepper in Bangka - Budi, Ferri Stya; Nurmansyah, Ali; Hartono, Arief; Widodo (Jurnal Fitopatologi Indonesia, 2024)
Analysis of the Correlation between Farmers' Cultivation and Soil-borne Diseases of Pepper in BangkaThe decrease in planted area and production of black pepper (Piper nigrum) in Bangka is influenced by soil-borne diseases such as yellow disease, basal rot disease, and white root disease. Soil-borne diseases are closely related to biotic and abiotic factors that trigger their development, such as cultivation techniques practiced by farmers. This study aims to identify distribution and cultivation techniques that trigger the development of soil-borne diseases in black pepper plants in Bangka. The study was conducted in the districts of South Bangka, Central Bangka, Bangka, and West Bangka in Province of Bangka Belitung Islands. Field data collection was conducted through observations of disease intensity and structured interviews with farmers. The analysis results are presented in cross-tabulation tables for each soil-borne disease with correspondence plots to see distribution of cultivation factor groups on disease incidence levels. The results showed that yellow disease is the dominant soil-borne disease of pepper plantations in Bangka Island, followed by basal rot and white root. Correspondence analysis using the chi-square test at α 0.05, the cultivation factors that were significantly correlated with the intensity of yellow disease were plant age, plant population, seedling source, planting pattern, organic matter, and shading. While the factors that significantly affect the intensity of basal rot are seedling source, shading, and sanitation. Vine prunning is closely related to the incidence of white root disease. Cultivation techniques have been identified as an important factor in the development of pepper soil-borne diseases in Bangka. Further research is needed to identify the interrelationships between these factors.